Aging Is a Risk Factor for Utricular Dysfunction in Idiopathic Benign Paroxysmal Positional Vertigo - Fujimoto, Chisato; Kawahara, Takuya; Kinoshita, Makoto; Kikkawa, Yayoi S.; Sugasawa, Keiko; Yagi, Masato; Yamasoba, Tatsuya; Iwasaki, Shinichi; Murofushi, Toshihisa (Frontiers in Neurology, 2018)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of balance disorders in the elderly. Dislodgement of the otoconia in BPPV might have an association with damage to the otolith organs. The aim of this study was to investigate whether aging is a risk factor for otolith organ dysfunction in idiopathic BPPV. We retrospectively reviewed the medical records of 112 consecutive idiopathic BPPV patients who underwent cervical VEMP testing to air-conducted sound (ACS cVEMP), ocular VEMP testing to bone-conducted vibration (BCV oVEMP) and caloric testing. We performed binomial logistic regression analyses to see whether age, the side affected by BPPV or the canal affected by BPPV have an association with the presence of peripheral vestibular dysfunction in idiopathic BPPV patients. The elderly group (aged ≥ 65 yrs) had a significantly positive association with abnormalities in BCV oVEMPs (p = .0109), while the side affected by BPPV (p = .598) and the canal affected by BPPV (p = .576) did not. The odds ratio of the abnormal BCV oVEMPs for the elderly group compared with the non-elderly group (aged < 65 years) was 2.676 (95% confidence interval, 1.254-5.079). The elderly group had no significant association with the abnormalities in ACS cVEMPs (p = .0955) or caloric testing (p = .488). Dysfunction of the utricle, where the dislodgement of the otoconia mainly occurs, is affected by aging in idiopathic BPPV.